2019
DOI: 10.1088/1748-9326/ab3306
|View full text |Cite
|
Sign up to set email alerts
|

The macroeconomic impacts of future river flooding in Europe

Abstract: The economic impacts of disasters can reach far beyond the affected regions through interconnected transboundary trade flows. As quantification of these indirect impacts is complex, most disaster risk models focus on the direct impacts on assets and people in the impacted region. This study explicitly includes the indirect effects via regional economic interdependencies to model economic disaster losses on a continental scale, exemplified by river flooding in Europe. The results demonstrate that economic impli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 39 publications
1
20
0
Order By: Relevance
“…For example, this has been estimated to account for 40% of the total damages in the case of Hurricane Katrina (Hallegatte, 2008 ). Longer term macroeconomic effects of disasters can be both positive and negative (Lazzaroni & van Bergeijk, 2014 ), and one major uncertainty thereby is the economic dynamics of recovery after the event (Koks et al., 2019 ). We do not consider these effects here, because their assessment relies on wider assumptions on the whole economy, which cannot be covered in this study.…”
Section: Discussionmentioning
confidence: 99%
“…For example, this has been estimated to account for 40% of the total damages in the case of Hurricane Katrina (Hallegatte, 2008 ). Longer term macroeconomic effects of disasters can be both positive and negative (Lazzaroni & van Bergeijk, 2014 ), and one major uncertainty thereby is the economic dynamics of recovery after the event (Koks et al., 2019 ). We do not consider these effects here, because their assessment relies on wider assumptions on the whole economy, which cannot be covered in this study.…”
Section: Discussionmentioning
confidence: 99%
“…It is difficult to include transboundary effects in the AIM/CGE model, because modeling the effects requires data on the economics actually affected and unaffected by the flood. Some studies (e.g., Koks et al, 2019) developed models to account for transboundary and cross‐country effects in Europe using data consisting of multiregional supply‐use tables and bilateral trade in the region. However, no such detailed data set is available for our target region.…”
Section: Discussionmentioning
confidence: 99%
“…Such estimations on continental and global scales are difficult due to the limited availability of data on capital and labor for each sector. At continental and global scales, the indirect economic losses have been estimated using a computable general equilibrium (CGE) model (Ciscar et al, 2011; Dottori et al, 2018) and a deterministic loss‐propagation model (Koks et al, 2019; Willner et al, 2018). For example, Dottori et al (2018) estimated welfare losses using a CGE model and found that welfare losses will increase with increases in human losses, and economic damage with increased global warming.…”
Section: Introductionmentioning
confidence: 99%
“…They represent approximately one-third of all global hazardous events, and the number of extreme flood incidences has significantly increased over the past few decades [2]. Every year this type of hazard causes a significant loss of life and property [3] and severely affects the natural and human environment as well as the development of an area [4].…”
Section: Introductionmentioning
confidence: 99%